2011
DOI: 10.1128/jvi.00859-10
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Bovine Viral Diarrhea Virus RNA Synthesis by Thiosemicarbazone Derived from 5,6-Dimethoxy-1-Indanone

Abstract: In the present work, we described the activity of the thiosemicarbazone derived from 5,6-dimethoxy-1-indanone (TSC), which we previously characterized as a new compound that inhibits bovine viral diarrhea virus (BVDV) infection. We showed that TSC acts at a point of time that coincides with the onset of viral RNA synthesis and that it inhibits the activity of BVDV replication complexes (RCs). Moreover, we have selected five BVDV mutants that turned out to be highly resistant to TSC but still susceptible to rib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 29 publications
(33 reference statements)
0
42
0
7
Order By: Relevance
“…Similarly, two recently identified inhibitors target the template RNA binding channel on the fingers domain of denguevirus (Niyomrattanakit et al, 2010) and bovine viral diarrhea virus (Castro et al, 2011) polymerases, and mutational studies suggest there are inhibitor binding pockets on the dengue polymerase thumb domain that can interfere with initiation of genomic RNA synthesis (Zou et al, 2011). Unlike the small picornaviral polymerases that carry out primer-dependent initiation, these larger RdRPs are capable of de novo initiation and undergo large conformational changes in their thumb domain during the transition to an elongation complex.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, two recently identified inhibitors target the template RNA binding channel on the fingers domain of denguevirus (Niyomrattanakit et al, 2010) and bovine viral diarrhea virus (Castro et al, 2011) polymerases, and mutational studies suggest there are inhibitor binding pockets on the dengue polymerase thumb domain that can interfere with initiation of genomic RNA synthesis (Zou et al, 2011). Unlike the small picornaviral polymerases that carry out primer-dependent initiation, these larger RdRPs are capable of de novo initiation and undergo large conformational changes in their thumb domain during the transition to an elongation complex.…”
Section: Discussionmentioning
confidence: 99%
“…Некоторые исследованные азосоединения, тиосемикарбазоны и 2-фенилбензимидазол также подавляли репликацию BVDV в условиях in vitro, воздействуя на RdRp [28][29][30][31].…”
Section: Introductionunclassified
“…Recently, we have reported that b-isatin-N,N 0 -thiocarbohydrazone derivatives could have antimicrobial and antioxidant activity (Kiran et al, 2012a). Thiosemicarbazones were the first antiviral compounds recognized to possess broad-spectrum antiviral activity against a range of DNA and RNA viruses [Castro et al, 2011]. Earlier reports have described antiviral activity of isatin-b-thiosemicarbazone and isatin-b-semicarbohydrazone against different viral strains [Quenelle et al, 2006;Pandeya et al, 2005].…”
Section: Introductionmentioning
confidence: 99%